Supplementation with inulin reverses cognitive flexibility alterations and modulates the gut microbiota in high-fat-fed mice - González-Velázquez, Gabriela; Aguirre-Garrido, José Félix; Oros-Pantoja, Rigoberto; Salinas-Velarde, Isidro Daniel; Contreras, Irazú; Estrada, José Antonio; Soto-Piña, Alexandra Estela (Frontiers in Behavioral Neuroscience, 2024)
Introduction Alterations in cognitive performance are associated with inadequate nutritional states and diet composition. Prebiotics, such as inulin, are substances that can modulate the gut microbiome and, consequently, brain function by producing metabolites such as short-chain fatty acids (SCFAs). This study aimed to evaluate the effect of supplementation with inulin on cognitive flexibility, body composition, and gut microbiota in a murine model exposed to a high-fat (HF) diet. Methods CD1 mice were divided into five groups: control fed a standard diet (C), high-fat diet (HF), inulin (I), high-fat diet with inulin (HFI), and manipulation control (M). Dietary supplementation was administered for 6 weeks. Cognitive flexibility was assessed using the Attentional Set-Shifting Test (AST). In addition, body composition was measured via electrical bioimpedance and adipose tissue compartments of each mouse were removed and weighed. Finally, gut microbiota metataxonomic was analyzed through metataxonomic bacterial 16S rRNA sequencing. Results We observed that HF group required more AST trials than the C, HFI, and I groups in the compound discrimination (CD) and extra-dimensional (ED) stages. Notably, the HFI group required fewer trials than the HF group in the ED stage (p = 0.0187). No significant differences in overall body composition were observed between the groups. However, the percentage of gonadal and peritoneal adipose tissue was significantly higher in the HF and I groups compared to the C group. Statistically significant differences in alpha diversity for gut microbiota were observed using the Shannon, Simpson, and Chao1 indices. The I group showed a decrease in bacterial diversity compared to the HF group. While no differences were observed between groups in the phyla Bacillota and Bacteroidotes, Clostridium bacteria represented a lower proportion of sequences in the I group compared to the C group. Additionally, Lactobacillus represented a lower proportion of sequences in the HF group compared to the C and I groups. Discussion These findings suggest that supplementation with inulin could be a useful approach to mitigate the negative effects of an HF diet on cognitive flexibility and modulate gut microbiota composition.